Italian Influences in Karol Szymanowski’s Work - Masi, Leonardo (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
Like many other artists, Szymanowski was hugely attracted to Italy. In this article, I will briefly expose, firstly, the “Italian” tracks that can be found in the Polish composer’s music, and, secondly, the declarations on Italy in Szymanowski’s writings, in particular on his art and music, trying to relate these elements between them to see what image of Italian culture emerges. I will show how Szymanowski’s cultural environment remains German-based nevertheless looking for the lost unity between man, art and nature in the heritage of the Italian Renaissance.